Motors and engines and how they work - Weiss, Harvey (New York : Crowell, 1969)
Describes various kinds of modern engines, their sources of energy, and how to make a model of each.
Keywords: Power (Mechanics) -- Juvenile literature; Engines -- Juvenile literature; Engines; Power (Mechanics)